Compatibility of the entomopathogenic fungus Beauveria bassiana with tritlumuron - VÁSQUEZ-P., CARMEN A.; SALDARRAGA-O., YAMILLÉ; PINEDA-G.J, FABIO (Revista Colombiana de Entomología, 2004)
The  combined use  of chemical and  biological insecticides  presents  a promising and  rational alternative  to  control  insect pests of agricultura!  and   medica!  importance.  The  compatibilities of the lnra297,  Cenicafé.Bb9205 and  UdeA , strains  of the  fungus  B. bassiana  with  the  insecticide  Starycide  S.C. 480   Bayer" (trlflumuron).  a  chitin  synthesis  inhibitor  in  insects,  were evaluated.  Combinations  of three concentrations  of each  strain  of B. bassiana (3x105,  1x107  and  3x108   conidios/ml)  and  triflumuron (0,05 0,025 and  0,0125 µ,g/¡.d)  were  tested.  The  fungus  suspension was  used  as a control.  The  compatibility  of the  two  agents was  evaluated  based   on  conidial germination  in  a  solid  medium  (Sabouraud  dextrose agar) and  mycelial  growth in a liquid  medium.  Conidial  germination was  observed at 24  and  48  h and mycelial  growth at  7 days.  The  germinated  and  non-germinated  conidia  and  dry  mycelium  weight  were the variables used  in statistical analysis. The presence of triflumuron inhibited  neither conidial  germination nor mycelial  growth of B. bassiana,  demonstrating  the  compatibility.  However,  both conidial  germination and  mycelial growth  in  the  presence  of triflumuron varied among  the  three  fungal strains  that were evaluated.